Profitabilitas pada Bank Umum Syariah di Indonesia: Pengaruh Faktor Internal serta Pembiayaan UMKM Sebagai Variabel Intervening - Syahla Aidah Nur Rahmah; Tjetjep Djuwarsa; Endang Hatma Juniwati (Journal of Applied Islamic Economics and Finance, 2022)
This study analyzes the effect of Financing to Deposit Ratio, Non-Performing Financing, and Operational Efficiency Ratio on Return On Assets through MSME Financing at Islamic Commercial Banks in Indonesia. The population used is Islamic Banking in Indonesia. The research method used is quantitative research with path analysis using IBM SPSS Statistics 25 software. The data used is secondary data published by OJK during the period of 2016-2020. The results of this study indicate the following direct effects: FDR and NPF have no effect on ROA, BOPO and MSME financing have a significant negative effect on ROA, FDR has no effect on MSME financing, NPF and BOPO have a significant negative effect on MSME financing, while the indirect effect can be concluded that FDR has no effect on ROA through MSME financing, NPF has a significant positive effect on ROA through MSME financing, and BOPO has a significant positive effect on ROA through MSME financing.